Effectiveness of Glass Wastes as Powder on Some Hardened Properties of Concrete - Yassin, Mohammed Maher; Mahmoud, Akram Shakir; Hama, Sheelan M. (Al-Nahrain Journal for Engineering Sciences, 2019)
This paper present glass waste material reusing in concrete as partial replacement of cement. Some hardened properties like compressive and flexural strengths, modulus of elasticity and % absorption was made. The effect of glass powder on these properties was examined compared to reference specimens without glass powder. Five percentage was tested: 0%(reference), 10%, 15%, 20% and 25%. From tests results one can conclude that replacing cement partially by glass powder enhanced strengths of concrete (compression and flexural) up to 20% replacing level Using glass powder as partial replacement of cement improved strengths and modulus of elasticity of concrete. The %absorption decrease with increasing of glass powder content. The results show that utilization of waste glass as powder in concrete can reduce amount of cement which save cost besides its environmental benefits.